A method of phase formation of vocal sound at activities of a training choral collective - Kyfenko, Anna; Romanova, Tetyana (ScienceRise: Pedagogical Education, 2020)
The article is devoted to coverage of the stages of forming the vocal sound in a classroom training choir, united in the phase sequence. The feature of the first phase of the vocal sound formation is the creation of the psychological setting, which leads to the very essence of singers’ activity. The second phase is characterized by a change in sound timbre similitude. Enormous pressure is required from the central nervous system to concentrate the inner mental work and make coordination. The sign of the third phase is the appearance of higher positional sound. In the fourth phase, the singing actions are more dynamically stable and coordinated. The fourth phase is characterized by broad compact timbre sound, but something too heavy by the power. A characteristic feature of the fifth phase is the automation of vocal skills, the sound gets flexibility and plasticity. The mechanism of stabilization in the formation of vocal skills that ensure the accuracy, efficiency and stability of the movements of the articulatory apparatus is analyzed. We have substantiated the method of imitation as a psychological process, transformed in the active thinking work and implemented in practice.The basic points of the head of a choir are analyzed, including: work on rounding lighting the sound, singing properly on the organized breathing support, forming a unified manner of sounding voices. It is noted, that the complex interaction of breath, soft palate and larynx ensures the correct formation of the vocal sound. It is determined, that the sound acquires a full quality characteristic only due to the smoothing of the registers. The main criteria of the set, academic voice are characterized, namely: the presence of two singing forms and the work of two resonators, which are equally involved in the formation of both low and high sounds. The mechanism of voice synchronization in choral parts is characterized